A charity sale by the English Language Club entrepreneurs / Noor Azli Affendy Lee, Muhammad Aiman Abdul Halim and Nur Ilianis Adnan - Affendy Lee, Noor Azli; Abdul Halim, Muhammad Aiman; Adnan, Nur Ilianis (Academy of Language Studies, 2022)
A charity sale was organised by the English Language Club (ELC) of Universiti Teknologi MARA, Cawangan Pulau Pinang (UiTMCPP) at Laman Perdana in Permatang Pauh campus from 4th April 2022 to 7th April 2022. With the assistance and support of the Malaysian Academy of SME and Entrepreneurship Development (MASMED), the club managed to secure a booth for free to sell its own originally-designed limited edition merchandise items for the purpose of raising funds to be donated to two organisations–Maahad Riyadhil Quran (MRIQ), Kedah and Zoo Taiping, Perak. Those organisations were chosen for our University Social Responsibility (USR) projects for the March – August 2022 semester: the Madrasah Visit and Exchange of Knowledge project and the Wildlife Conservation Week and Taiping Zoo Volunteer and Visit project respectively. Another purpose for the charity sale was to give exposure to club members on the responsibilities shouldered by common entrepreneurs in Malaysia.